2017
DOI: 10.1039/c7ta03735j
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced oxygen reduction reaction performance on PtSn nanowires: the importance of segregation energy and morphological effects

Abstract: In this study, the reaction mechanism and electrochemical properties of carbon-supported PtSn nanomaterials including nanoparticles and nanowires (NWs) toward the oxygen reduction reaction (ORR) have been investigated computationally and experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 54 publications
1
32
0
1
Order By: Relevance
“…Additionally, PtSn bimetallic nanoparticles supported on carbon-based materials promoted the oxidation of methanol [32] and ethanol [33] and exhibited enhanced lifetime [32], which led the PtSn nanoparticles to be selected as a promising catalyst for the ORR. PtSn nanoparticles and nanowires showed an increased performance; however, the decay in the mass activity for the catalysts was considerable [34]. Enhanced electrical conductivity of SnO 2 has been achieved by introducing small percentages of dopant elements [6,22,25,[35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PtSn bimetallic nanoparticles supported on carbon-based materials promoted the oxidation of methanol [32] and ethanol [33] and exhibited enhanced lifetime [32], which led the PtSn nanoparticles to be selected as a promising catalyst for the ORR. PtSn nanoparticles and nanowires showed an increased performance; however, the decay in the mass activity for the catalysts was considerable [34]. Enhanced electrical conductivity of SnO 2 has been achieved by introducing small percentages of dopant elements [6,22,25,[35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Massive research efforts have been made to develop active and durable oxygen reduction reaction (ORR) catalysts, which is recognized as a key issue in polymer electrolyte membrane fuel cell (PEMFC) technology. Pt-based alloy nanoparticles can exhibit significantly improved activity compared with pure Pt and are considered as one of the most important groups of ORR catalysts. Mechanistic studies discovered that the activity improvement can be attributed to alloy-composition-induced modification of the electronic and geometric structure of surface Pt atoms, which serve as the active sites. , A large variety of Pt alloy nanoparticle catalysts have been prepared and investigated in the past decades, aiming at achieving higher ORR activity. , However, it appeared challenging to achieve further breakthroughs in the activity improvement since the Pt 3 Ni­(111) study which was reported over 10 years ago . This research difficulty could be explained using the recently discovered scaling relationship, which suggests that lowering the energy barrier of a certain step in the reaction pathway on an active site would result in increasing the barrier of other steps on the same site. ,, This implies the existence of a minimum energy barrier that can be achieved in sole-site catalysis and provides a plausible explanation for catalyst research in many reactions, for instance, selective methane oxidation, ammonia synthesis, and dehydrogenation .…”
mentioning
confidence: 99%
“…As displayed in Figure a, all CV curves exhibit the characteristic peaks associated with adsorption/desorption of hydrogen, within 0.05–0.40 V, and the Pt oxide formation/reduction (except for Ir black), between 0.70 and 1.00 V. The hydrogen peak is more pronounced for catalysts with higher Ir content, except for Pt 55 @Ir 45 , which implies that the contribution of Ir to the adsorption/desorption of hydrogen is greater than that of Pt. Generally, the electrochemically active surface area ( A ecsa ) of Pt species is calculated through the integration of the charge related to the hydrogen underpotential deposition ( H upd ) . Herein, to avoid A ecsa over‐estimation of Pt in respect to Ir, the CV curves used for A ecsa calculations were recorded after 60 cycles within 0.05–1.42 V, to make sure the majority of Ir was oxidized to IrO x , which is inert to H upd (Figure d).…”
Section: Resultsmentioning
confidence: 99%